Analisis PIECES dalam Implementasi Kebijakan E-Learning di IAIN Kendari - Ambar Sri Lestari; Shbarur Rijal Hamka (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2019)
This study aims to analyze the implementation of e-learning policies at IAIN Kendari. Using a qualitative descriptive method, the data was collected through observation at the online page of https://elearning.iainkendari.ac.id, interviews and documentation. The results of PIECES analysis calculations in the application of e-learning are seen from several aspects, including: performance, information, economy, control and services are in the category of important with the value of 3.46%, 3.82%, 3.77%, 3.85% and 3.88% respectively. Regarding the aspect of efficiency, the value is 4.28% within the category Very Important. Whereas, the implementation of e-learning learning policies using Edward's theory was investigated from four aspects, namely: 1) communication that was conducted through the socialization of e-learning workshops; 2) resources including human/technician resources that were still very lacking as well as infrastructure with the addition of 80 Mbps bandwidth to five faculties, rectorates, libraries and postgraduate programs; 3) dispositions were given to the policy users, namely lecturers who were still less motivated in using e-learning, and 4) bureaucratic structure related to operational standards procedures that was designed in the form of e-learning guidebooks. The result found that e-learning implementation was in the category of important in the aspect of performance, information, economics, control and service, and in the category of very important in the aspect of efficiency. E-learning system at IAIN Kendari is acceptable for all academic civity, however they need personal motivation to implement and utilize it for classroom learning supported by speed internet access.